2017
DOI: 10.1002/ece3.3464
|View full text |Cite
|
Sign up to set email alerts
|

Global population structure and adaptive evolution of aflatoxin‐producing fungi

Abstract: Aflatoxins produced by several species in Aspergillus section Flavi are a significant problem in agriculture and a continuous threat to human health. To provide insights into the biology and global population structure of species in section Flavi, a total of 1,304 isolates were sampled across six species (A. flavus, A. parasiticus, A. nomius, A. caelatus, A. tamarii, and A. alliaceus) from single fields in major peanut‐growing regions in Georgia (USA), Australia, Argentina, India, and Benin (Africa). We inferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…Hybridization and introgression may be important forces for interspecific dispersal of biosynthetic genes in fungi and in diversifying and generating novel metabolites (Olarte et al ., ; Moore et al ., ; Hubka et al ., ). Although the number of available genomes of echinocandin‐producing fungi precludes a detailed analysis, interspecific hybridization and introgression could have played a role in interspecific dispersion of the echinocandin BGCs, at least in species complexes where closely related species produce echinocandins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization and introgression may be important forces for interspecific dispersal of biosynthetic genes in fungi and in diversifying and generating novel metabolites (Olarte et al ., ; Moore et al ., ; Hubka et al ., ). Although the number of available genomes of echinocandin‐producing fungi precludes a detailed analysis, interspecific hybridization and introgression could have played a role in interspecific dispersion of the echinocandin BGCs, at least in species complexes where closely related species produce echinocandins.…”
Section: Discussionmentioning
confidence: 99%
“…Section Nidulantes encompasses a large complex of rapidly evolving species, with both homothallic and heterothallic species, consequently, interspecific dispersal of BGCs and their chemical evolution in part may be driven by hybridization and introgression as has been observed in the A . flavus complex (Olarte et al ., ; Moore et al ., ), and section Fumigati (Hubka et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Crossing over and independent assortment of A. flavus chromosomes in laboratory crosses (Horn et al, 2009a;Olarte et al, 2012Olarte et al, , 2015 where the fertility of parental strains inferred from these crosses appears to be borne out under field conditions (Horn et al, 2016). This direct evidence is corroborated by numerous population genetics studies that go back to 1998 providing indirect evidence of recombination in field populations of A. flavus worldwide (Geiser et al, 1998(Geiser et al, , 2000Moore et al, 2009Moore et al, , 2013Moore et al, , 2017Ramirez-Prado et al, 2008) and among closely related aflatoxin-producing species (Carbone et al, 2007a(Carbone et al, , 2007bHorn et al, 2009bHorn et al, , 2009cHorn et al, , 2011.…”
Section: Evidence For Sexual Reproduction In a Flavusmentioning
confidence: 83%
“…There are many drawbacks and limitations in using microsatellites as genetic markers in the studies reported in the commentary Cotty, 2010, 2015; particularly when it comes to the analysis and interpretation of recombination (Putman and Carbone, 2014), as pointed out in a recent A. flavus population genetic study using the same set of microsatellite markers (Drott et al, 2019;Grubisha and Cotty, 2009). Again, this emphasizes the importance of examining single nucleotide polymorphisms from multiple loci (Geiser et al, 1998(Geiser et al, , 2000Moore et al, 2009Moore et al, , 2013Moore et al, , 2017Okoth et al, 2018;Taylor et al, 1999) and genome-wide (Molo, 2018) for determining patterns and rates of recombination in populations of A. flavus.…”
Section: Evidence For Sexual Reproduction In a Flavusmentioning
confidence: 99%
“…The fungi were isolated on modified dichloran-rose bengal (MDRB) agar medium ( 6 ), restreaked onto MDRB agar, from which hyphal tips of single colonies were transferred to slants of Czapek’s medium ( 7 ), and identified following a previously described protocol ( 8 ). Cluster analysis of the genetic fingerprints of the isolates using the 25 insertion/deletion markers within the aflatoxin biosynthesis pathway and a protocol published by Faustinelli et al ( 9 ) revealed several clades, from which 16 representative isolates (4 A. parasiticus strains, 5 A. flavus strains, 2 A. flavus L strains [ 10 ], and 5 A. flavus S strains [ 10 ]) were chosen for whole-genome sequencing, as reported in Table 1 . DNA was extracted from spores and sclerotia using the DNeasy plant minikit (Qiagen, Valencia, CA) after growth of the isolates on MDRB agar for 3 days in the dark at 30°C.…”
Section: Announcementmentioning
confidence: 99%